2004
DOI: 10.1002/cncr.20308
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of zoledronic acid in the treatment of skeletal metastases in patients with nonsmall cell lung carcinoma and other solid tumors

Abstract: BACKGROUNDThe authors previously reported the efficacy of a dose of 4 mg of zoledronic acid in reducing skeletal complications in patients with bone metastases secondary to lung carcinoma and other solid tumors (except carcinomas of the breast and prostate). In the current study, they update these results and report the long‐term efficacy and safety of 21 months of treatment with zoledronic acid in a randomized, placebo‐controlled trial.METHODSA total of 773 patients were randomized to receive zoledronic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
492
2
33

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(539 citation statements)
references
References 15 publications
12
492
2
33
Order By: Relevance
“…At present, there is no such suitable data set. Alternatively, patients from the pamidronate arm of the Rosen trial [18,19,26] could be used, but this is less than optimal because risks and risk factors may be different in this group of patients, pamidronate is now used less often, and ZOL produced some significant SRE benefits beyond those produced by pamidronate [11,19]. A further challenge in validation of models for risk classification of SREs is the presence of the competing risk for death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no such suitable data set. Alternatively, patients from the pamidronate arm of the Rosen trial [18,19,26] could be used, but this is less than optimal because risks and risk factors may be different in this group of patients, pamidronate is now used less often, and ZOL produced some significant SRE benefits beyond those produced by pamidronate [11,19]. A further challenge in validation of models for risk classification of SREs is the presence of the competing risk for death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bisphosphonates are now standard therapy in patients with bone metastases from BC [6]. Particularly, the large, multicenter, randomized, placebo-controlled trials of zoledronic acid (ZOL) demonstrated reduction in the frequency of SREs versus placebo in BC patients [7], and also in patients with castration-resistant prostate cancer [8,9] and a broad range of other solid tumors, including lung cancer [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this recent increase in treatment options, a significant proportion of patients will eventually develop symptoms of bone progression during the course of the disease [6]. In fact, overall, bone metastases and their skeletal-related events are not controlled in approximately 20-40% of cancer patients [7][8][9], and the current therapeutic regimens leave B45% of patients with inadequate or undermanaged pain control [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…19 A retrospective analysis of a phase III study suggested that ZA therapy may improve survival in a subgroup of lung cancer patients with high bone turnover when compared with placebo. 20,21 Another study showed better survival with ZA over clodronate in newly diagnosed multiple myeloma patients. 22 The present study retrospectively examined the outcomes of ZA treatment in a population of US veterans with bone-metastatic prostate cancer.…”
Section: Introductionmentioning
confidence: 99%